Educational report: A case of lacrimal sac rhinosporidiosis. (2nd September 2016) - Jamison, Aaron; Crofts, Kevin; Roberts, Fiona; Gregory, Maria Elena
ABSTRACT: This article reports a presentation of lacrimal sac rhinosporidiosis and informs the reader of this uncommon but important diagnosis. A 36-year-old man from Pakistan presented with a 3-month history of swelling at the nasal aspect of the left lower lid. This was associated with occasional crepitus and slight localised discomfort, but no epiphora. There was a palpable fullness near the left medial canthus associated with telecanthus but a normal sac washout and normal eye examination otherwise. Previous medical history included an ipsilateral nasal polypectomy and inferior meatal antrostomy around 10 years previously, whilst living in Pakistan. Various imaging modalities were useful in identifying a soft tissue mass within the left nasolacrimal duct. Following excision biopsy, histological examination confirmed the presence of rhinosporidiosis, likely caused by the organism Rhinosporidium seeberi . Rhinosporidiosis should be considered as a potential cause in any case of lacrimal sac pathology. Imaging studies may be helpful in measuring the extent of disease, although histological examination is required to confirm the diagnosis. Although rare, the complications of rhinosporidiosis can be potentially blinding or fatal. As discussed in this case, the presence of telecanthus may represent a lacrimal system tumour, either malignant or benign, and should always prompt further investigation.